Elementos para una metodología del estudio de la calidad de vida (2004)
ABSTRACT: Based on the Survey of Quality of Life of year 1997, elaborated by Metropolitan Planning, Brown, Correa and Salazar (1998) they designed an indicator that allowed to know for the first time the conditions of life of the homes in the city of Medellín. This indicator, denominated Indicating of quality of life (ICV), is a summary of different characteristics of the house and the people who compose the home, such as services to the house, human capital and social security, demographic aspects and quality of the house. In the construction of the ICV variable statistical techniques were used qualitative that allowed to use of way optimal as much as quantitative related to the quality of life, forms such that the ICV had Maxima information of them. The used procedures are circumscribed the techniques of optimal quantification and the analysis nonlinear of main Components.